"UN MANIFIESTO A LA MUJER BRASILEÑA": GRUPO FEMENINO DE ESTUDIOS SOCIALES Y ACTUACIÓN DE LAS MUJERES EN LA PRENSA - da Silva, Marcelo Gomes (2020)
The objective of this work is to analyze the performance of teachers in the Rio press in the context of the First Republic. For that, it was necessary to understand the conditions and norms in which the women were subject in that period. From the elucidation of the role attributed to women, it was possible to perceive that the teaching profession has become an important space of female occupation. In this sense, the “Manifest to the Brazilian Woman”, published in the newspaper Voz do Povo in 1920 by the Women’s Social Studies Group, was selected as the guiding principle of the study, with the presence of female teachers in its composition. Among the contents included in the manifest were the discussions on “women’s emancipation”, aimed at freeing women from the "various forms of bondage" to which they were subjected. In order to problematize the debate held, we also sought to analyze the visibility given to the discourses of teachers in the newspapers Correio da Manhã and A Razão. The research allowed to observe relevant aspects of the experience of women taken as subjects of the history of that historical moment.